Taguchi-based and intelligent optimisation of a multi-response process using historical data - Šibalija, Tatajana (Strojniški vestnik, 2011)
Optimisation of manufacturing processes is typically performed by utilising mathematical process models or designed experiments. However, such approaches could not be used in the case when explicit quality function is unknown and when actual experimentation would be expensive and time-consuming. The paper presents an approach to optimisation of manufacturing processes with multiple potentially correlated responses, using historical process data. The integrated approach is consisted from two methods: the first relays on Taguchis quality loss function and multivariate statistical methods, the second method is based on the first one and employs artificial neural networks and a genetic algorithm to ensure global optimal settings of a critical parameters found in a continual space of solutions. The case study of a multi-response process with correlated responses was used to illustrate the effective application of the proposed approach, where historical data collected during normal production and stored in a control charts were used for process optimisation.
Keywords: genetic algorithm; genetski algoritem; historical data; neural networks; nevronske mreže; optimisation; optimizacija; predhodni podatki; Taguchi method; Taguchi metoda